Factors Affecting Days Open among Smallholder Dairy Cattle in Uasin Gishu County, Kenya - K. Philip , Biamah; Joseph , Omega; K, David , Kios (African Journal of Education,Science and Technology (AJEST), 2021)
The dairy industry in Uasin Gishu County (UGC) provides nutrition and employment among Smallholder dairy Farmers (SDF). The reproductive and productive potential of dairy cattle within the recommended range 85-110 days open (DO) ensures a calf per year. The study sought to determine factors influencing DO among SHF in UGC. 216 cows were purposively selected and artificially inseminated in the three agro-ecological zones (AEZ) of UGC. Further selection DO on 116 was determined. Focus group discussions (FGD) and interviews of key informants (KI)were held, in DO data. Data from the animals was subjected to t-tests to establish the differences within AEZ, breeds, farming systems, and conception status while Information from the FGDs was presented descriptively. Mean DO for AEZ 3 of 206 ± 20 days was significantly lower than those of AEZ 1, 303 ± 35 and AEZ 2, 281 ± 34. Mean DO for Ayrshire, Friesian and Zebu cross of 264 ± 30, 258 ± 28 and 244 ± 24 days respectively weren’t significantly different as of 227 ± 34 for intensive farming systems and 260 ± 20 days for semi-intensive farming. DO for cows confirmed in-calf was 237 ± 21 and those that weren’t, was 279 ± 27 days. The average DO (255 ± 17) was significantly longer than 85-110 days. High cost of feeds, poor record-keeping, and inadequate Veterinary services (VS) resulted from the FGDs and interviews of KI. Inadequate VS forced farmers to handle dystocias and other obstetrics complications resulting in post-parturient metritis and consequently, prolonged DO. Other factors included poor management of cows in the first 100 days in milk, poor record-keeping, irregular supplementation, and inadequate extension services. Good nutrition after pregnancy and veterinary and extension services are necessary for a calf-per-year-per cow.